PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 -2022 - intan zagita putri; Will Andilla Darniaty (Ibs Press, 2024)
The research studied aims to determine the effect of financial performance using profitability proxied by Return On Assets (ROA), liquidity proxied by Current Ratio (CR), leverage proxied by Debt to Equity Ratio (DER), and company size proxied by SIZE. The sample in this study is retail companies that have been listed on the Indonesia Stock Exchange from 2020 – 2022. This study uses secondary data in the form of annual financial reports obtained from the Indonesian stock exchange website. Data analysis was carried out by multiple linear regression. The results showed that financial performance using the profitability ratio had no effect on the timeliness of submitting financial reports, liquidity and company size showed that it had a positive effect on the timeliness of submitting financial reports. And leverage shows that it has a negative effect on the timeliness of submitting financial reports.